Garlic ameliorates atherosclerosis by regulating ferroptosis pathway: an integrated strategy of network pharmacology, bioinformatic and experimental verification - Gao, Tingting; Gao, Siqi; Wang, Heng; Wang, Shule; Li, Lizheng; Hu, Jie; Yan, Sheng; Zhang, Ruijing; Zhou, Yun; Dong, Honglin (Frontiers in Pharmacology, 2024)
Background: Atherosclerosis (AS) is a chronic arterial pathology and a leading cause of vascular disease-related mortality. Fatty streaks in the arterial wall develop into atherosclerosis and characteristic plaques. Clinical interventions typically involve lipid-lowering medications and drugs for stabilizing vulnerable plaques, but no direct therapeutic agent specifically targets atherosclerosis. Garlic, also locally known as DASUAN, is recognized as a widely sold herbal dietary supplement esteemed for its cardiovascular benefits. However, the specific mechanisms of garlic's anti-atherosclerotic effects remain unclear. Aims: This study aims to elucidate the pharmacological mechanisms through which garlic ameliorates atherosclerosis. Methods: The study identified the major active components and targets of garlic by screening the TCMSP, TCM-ID, and ETCM databases. Atherosclerosis-associated targets were obtained from the DisGeNET, GeneCards, and DiGSeE databases, and garlic intervention targets were determined through intersection. Utilizing the intersected genes, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were conducted using R software. A garlic component-disease target network was constructed using Cytoscape. RNA-seq datasets from the GEO database were utilized to identify differentially expressed genes (DEGs) associated with atherosclerosis. The target genes were intersected with DEGs and the FerrDb (ferroptosis database). Molecular docking predicted the binding interactions between active components and the core targets. In vitro and in vivo experiments validated the identified core targets. Results: The integration of garlic drug targets with atherosclerotic disease targets identified 230 target genes.Intersection with RNA-seq DEGs revealed 15 upregulated genes, including 8 target genes related to ferroptosis. Molecular docking indicated favorable affinities between garlic active components (Sobrol A, (+)-L-Alliin, Benzaldoxime, Allicin) and target genes (DPP4, ALOX5, GPX4). Experimental validation showed that GARLIC reduces the expression of ferroptosis-related genes in AS, suggesting its therapeutic potential through the regulation of ferroptosis. Conclusion: Garlic ameliorates atherosclerosis by targeting intra-plaque ferroptosis and reducing lipid peroxidation. These findings provide novel insights into the pharmacological mechanisms underlying the efficacy of garlic in treating AS.